Government Roles in Village Budget Assistance by DPMD Sidoarjo Regency: Peran Pemerintah dalam Bantuan Anggaran Desa oleh Dinas Pembangunan Masyarakat dan Desa (DPMD) Kabupaten Sidoarjo - Alif, Deftyana Ainnur; Choiriyah, Ilmi Usrotin (Indonesian Journal of Cultural and Community Development, 2025)
Background: Village governments in Indonesia hold strategic roles in rural development through financial independence. The preparation of the Village Revenue and Expenditure Budget (APBDes) is a vital process to ensure transparent and accountable fiscal management. Specific Background: In Sidoarjo Regency, the Department of Community and Village Empowerment (DPMD) assists villages in formulating the APBDes through regulation, facilitation, and supervision mechanisms. Knowledge Gap: However, limited human resources, uneven regulation implementation, and technical constraints have challenged the uniformity and timeliness of APBDes preparation. Aims: This study analyzes the roles of DPMD Sidoarjo as a regulator, dynamizer, facilitator, and catalyst in guiding the APBDes formulation process. Results: Findings indicate that DPMD performs all four roles effectively: updating regulations to local conditions, mobilizing community participation, providing training and technical assistance, and accelerating guideline issuance. Yet, obstacles remain due to funding limitations, inconsistent price standards, and incomplete representation of all villages. Novelty: The study offers a comprehensive understanding of DPMD’s multidimensional function in strengthening village fiscal capacity. Implications: These insights may guide policymakers in improving governance frameworks and ensuring sustainable village financial planning in other regions. Highlights:• Strengthened DPMD regulatory and facilitation roles• Uneven village participation and resource constraints• Policy synchronization improves local fiscal governance